Fracture properties of magnesium alloys AZ91D and AM50A - Wang, Wei. (2008)
In this project, four-point bending test was conducted on two important magnesium alloys AZ91D and AM50A at room temperature to obtain the fracture loads. Microscopic fracture stresses were calculated from the fracture loads. Metallographic and fratograhic observations were performed using optical microscope and scanning electron microscope.